Mixed dentition space analysis in a Jordanian population: comparison of two methods - E. S. J. ABU ALHAIJA, & M. A. QUDEIMAT (Paediatric Dentistry, 2006)
Space management during mixed dentition period involves evaluating the space requirements for unerupted permanent teeth, usually the canines and premolars.